A pharmacokinetic study and critical reappraisal of curcumin formulations enhancing bioavailability - Maurice A.G.M. Kroon; Hanneke W.M. van Laarhoven; Eleonora L. Swart; Olaf van Tellingen; E. Marleen Kemper (iScience)
Summary: This independent crossover study assessed curcumin bioavailability and excretion in nine healthy males receiving three formulations (AOV, Longvida, and NovaSOL) at about 570 mg, while AOV was also tested at 2280 mg, with and without piperine. Plasma levels of unconjugated curcumin remained below 2 nM in most cases, including high-dose AOV and piperine combinations. NovaSOL achieved the highest levels (6.7–38 nM at 30 min), but these rapidly declined and were still 100-fold lower than concentrations used in vitro to show biological effects. Curcumin conjugates exceeded 10 nM with all formulations, particularly NovaSOL, which showed 100-fold higher levels. Fecal recovery mainly included unconjugated curcuminoids and was high, except for NovaSOL, suggesting better intestinal absorption. However, even when using a formulation with enhanced uptake, plasma levels of unconjugated curcumin remained minimal. Piperine addition provided no benefit. The findings underscore that bioavailability claims should be based on unconjugated curcumin and not on its poorly membrane permeable conjugates.